Protective effects and its mechanism of garlicin on the renal function in type 1 diabetic rats - JIANG Jing; TANG Xiao-ling; YANG Jin (Linchuang shenzangbing zazhi)
Objective To explore the protective effects and its mechanism of garlicin on the renal function in type 1 diabetic rats. Methods After establishing the rat model of type 1 diabetes, these rats were randomly divided into normal control group（n=8）, diabetic group（n=11） and garlicin group（n=11）. With 4 weeks of garlicin intervention after modeling, the urine protein excretion and renal function were tested on all the rats, and oxidative stress level was measured by dihydroethidium（DHE） staining. The expression levels of various subunits and their mRNA of NAPH oxidase in the renal tissues were determined by RT-PCR and Western Blot. ELISA was used to test the activity of malonic dialdehyde（MDA） and superoxide dismutase（SOD）. Results Compared with those in normal rats, blood glucose, BUN, Scr and urinary albumin excretion were increased markedly in diabetic rats; however, in diabetic rats, endogenous creatinine clearance was reduced, oxidative stress and MDA in the renal tissues were increased significantly, the activity of SOD was downregulated, the mRNA and protein expression levels of the subunit p22phox of NADPH oxidase were upregulated markedly. After garlicin intervention, the above indices were improved notably. Conclusions Garlicin may play a protection role of the renal function in diabetic rats by reducing the oxidative stress level in the renal tissues of diabetic rats.